An exploratory study of entrepreneurial leadership development of university students - Bagheri, Afsaneh; Lope Pihie, Zaidatol Akmaliah (Eurojournals, 2009)
University entrepreneurship programs play fundamental roles in developing entrepreneurial qualities of students. However, little is known about the contributions of such programs in developing students’ entrepreneurial leadership capabilities. A qualitative research was conducted to explore the roles of entrepreneurship programs of University Putra Malaysia in developing students’ entrepreneurial leadership. Two student entrepreneurial leaders who are actively involved in entrepreneurial leadership activities through holding the leadership positions of the university entrepreneurship clubs and also participated in the university entrepreneurship development courses were purposefully selected as the participants of this study. The semi-structured interview data analysis indicates that the university entrepreneurship development programs facilitate entrepreneurial leadership development of students in many ways including experiential learning, social interaction learning, and opportunity recognition. Moreover, entrepreneurial leadership development occurs in a process of transforming the knowledge acquired from experience and social interaction to identify the opportunities for personal development and business creation. Implication of the findings and suggestions for improving university entrepreneurship programs are presented in the closing section of this paper.